ANALISIS MUBTADA’ DAN KHOBAR DALAM KITAB SAFINATUN NAJA KARYA SYAIKH SALIM BIN SUMAIR AL-HADROMY - Khoyir Nuron Nafi’ah; Asni Furoidah (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This study aims to analyze the syntactic structure and semantic implications of mubtada’ and khabar in fiqh texts, particularly in the book Safīnatun Naja by Syaikh Salim bin Sumair Al-Hadrami. This research employs a qualitative descriptive approach based on library research, utilizing content analysis techniques that integrate syntactic and semantic analysis. The data consist of sentences containing mubtada’ and khabar structures, comprising a total of 182 instances of mubtada’ and 183 instances of khabar. The findings reveal that mubtada’ is predominantly realized in the form of isim ẓāhir (178 instances), followed by 4 instances of ḍamīr, 1 instance of maḥżūf, and 2 instances of mubtada’ mu’akhkhar. Meanwhile, khabar is dominated by the mufrad form (158 instances), followed by 15 instances of syibh jumlah and 10 instances of jumlah fi‘liyah, with no occurrence of jumlah ismiyyah. In addition, the influence of nawāsikh is identified, including kāna wa akhwātuhā (30 instances) and inna wa akhwātuhā (3 instances), which affect the i‘rāb structure of sentences. Semantically, the variation in khabar forms reflects differences in meaning, such as processual meaning in jumlah fi‘liyah, limitation in negative constructions, and contextual meaning in syibh jumlah. These findings indicate that the structure of mubtada’ and khabar functions not only as a grammatical component but also plays a significant role in constructing and clarifying legal meaning in fiqh texts. ABSTRAK Penelitian ini bertujuan untuk menganalisis struktur sintaksis dan implikasi semantik mubtada’ dan khabar dalam teks fikih, khususnya dalam kitab Safīnatun Naja karya Syaikh Salim bin Sumair Al-Hadrami. menggunakan pendekatan deskriptif kualitatif berbasis penelitian kepustakaan (library research) dengan teknik analisis isi yang mengintegrasikan analisis sintaksis dan semantik. Data berupa kalimat-kalimat yang mengandung struktur mubtada’ dan khabar, dengan total 182 data mubtada dan 183 data khabar. Hasil penelitian menunjukkan bahwa mubtada’ didominasi oleh isim ẓahir sebanyak 178 data, diikuti 4 data ḍamīr, 1 data maḥżūf, dan 2 data mubtada mu’akhkhar. Sementara itu, khabar didominasi oleh bentuk mufrad sebanyak 158 data, diikuti 15 data syibh jumlah dan 10 data jumlah fi‘liyah, serta tidak ditemukan khabar jumlah ismiyyah. Selain itu, ditemukan pengaruh nawāsikh berupa kāna wa akhwātuhā (30 data) dan inna wa akhwātuhā (3 data) yang memengaruhi struktur i‘rāb kalimat. Secara semantik, variasi bentuk khabar menunjukkan perbedaan makna, seperti makna proses pada jumlah fi‘liyah, pembatasan pada struktur negasi, serta makna kontekstual pada syibh jumlah. Temuan ini menunjukkan bahwa struktur mubtada’ dan khabar tidak hanya berfungsi secara gramatikal, tetapi juga berperan penting dalam membentuk dan memperjelas makna hukum dalam teks fikih.